2022
DOI: 10.1186/s13567-022-01039-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Streptococcus suis genomes identifies novel candidate virulence-associated genes in North American isolates

Abstract: Streptococcus suis is a significant economic and welfare concern in the swine industry. Pan-genome analysis provides an in-silico approach for the discovery of genes involved in pathogenesis in bacterial pathogens. In this study, we performed pan-genome analysis of 208 S. suis isolates classified into the pathogenic, possibly opportunistic, and commensal pathotypes to identify novel candidate virulence-associated genes (VAGs) of S. suis. Using chi-square tests and LASSO regression models, three accessory pan-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…Some recent studies have undertaken whole-genome sequencing (WGS) in combination with comparative genomic approaches to evaluate the genomic diversity and AMR elements harbored by S. suis isolates ( Weinert et al, 2015 ; Wileman et al, 2019 ; Hadjirin et al, 2021 ; Estrada et al, 2022 ). The majority of these genomic sequences needed to evaluate potential risks attributed to the capacity of S. suis isolates to successfully function as zoonotic agents and/or reservoirs for AMR dissemination, is derived from isolates obtained outside the U.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have undertaken whole-genome sequencing (WGS) in combination with comparative genomic approaches to evaluate the genomic diversity and AMR elements harbored by S. suis isolates ( Weinert et al, 2015 ; Wileman et al, 2019 ; Hadjirin et al, 2021 ; Estrada et al, 2022 ). The majority of these genomic sequences needed to evaluate potential risks attributed to the capacity of S. suis isolates to successfully function as zoonotic agents and/or reservoirs for AMR dissemination, is derived from isolates obtained outside the U.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these genomic sequences needed to evaluate potential risks attributed to the capacity of S. suis isolates to successfully function as zoonotic agents and/or reservoirs for AMR dissemination, is derived from isolates obtained outside the U. S ( Weinert et al, 2015 ; Wileman et al, 2019 ; Hadjirin et al, 2021 ; Estrada et al, 2022 ). The goals of the current study were to fill this gap by utilizing whole-genome sequencing (WGS) analysis to evaluate the sequence type (ST) and serotype distribution of S. suis isolates obtained within the U.S., screen genomes for genomic elements encoding AMR, determine whether or not identified AMR genes are located within MGEs, and screen for genomic elements encoding factors known to increase or contribute to the capacity of S. suis to transmit, colonize, and/or cause disease in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, analysis of the virulence-associated genes showed that many of them were present in the ST1 strain ID26154 ( Table 3 ). Three proposed novel marker genes ( SSU_RS03100 : hypothetical protein, SSU_RS09155 : hypothetical protein, and SSU-RS09525 : RNA-binding protein) for predicting the pathogenic pathotype of S. suis were also present in our ST1 strain (100% identity), suggesting these are also present in Asian or Eurasian strains ( Table 3 ; Estrada et al, 2022 ). However, further study needs to be evaluated for these marker genes with S. suis strains from different geographical origins.…”
Section: Resultsmentioning
confidence: 93%
“…Our ST104 strain contains genes that may be associated with virulence in the ST1 and ST7 strains, as shown in Table 3 ( Fittipaldi et al, 2012 ; Takamatsu et al, 2009 ; Zhang et al, 2009 ; Dumesnil et al, 2018 ). It carries three proposed novel marker genes ( SSU_RS03100 : hypothetical protein, SSU_RS09155 : hypothetical protein, and SSU-RS09525 : RNA-binding protein; Estrada et al, 2022 ) that predict pathogenicity of S. suis , suggesting that this ST104 strain presents a pathogenic pathotype ( Table 3 ; Estrada et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation